Edukasi Aktivitas Fisik Pada Ibu Hamil Di Desa Singopuran Melalui Media Audio Visual - Tiara Fatmarizka; Wahyu Tri Sudaryanto; Daris Tri Gamadia; Ilma Liani Vanath; Ivana Hanun Nisa (Universitas 45 Surabaya, 2023)
Physical activity is any body movements produced by skeletal muscles that require energy expenditure. Physical activity that can affect hemoglobin levels is in severe physical activity. This activity was held on May 26, 2023 at Singopuran Village Hall, Kartasura District, Sukoharjo Regency, Central Java using audio visuals namely Power Point, X-Banner, and Video of Physical Activity. The results obtained from activities in this community are pregnant women can add insight into the knowledge of physical activity through education using audio visuals namely PPT, X-Banner, and Video of Physical Activity Proven from increasing the evaluation value carried out. The conclusion is that the use of audio visual media has a very good impact in increasing the knowledge of pregnant women about physical activity